Genital Human Papillomavirus Prevalence Over the Lifespan Among Females and Males in a National Cross-Sectional Survey, United States, 2013–2016. Issue 11 (November 2021) - Lewis, Rayleen M.; Gargano, Julia W.; Unger, Elizabeth R.; Querec, Troy D.; Markowitz, Lauri E.
Abstract : Background: Patterns of human papillomavirus (HPV) prevalence by age differ by sex. To further the descriptive epidemiology of genital HPV, we analyzed prevalence by age for nonvaccine (non–4vHPV) type and vaccine (4vHPV) type HPV by sex using 2013–2016 National Health and Nutrition Examination Survey data, the first 4 years of national data from both sexes. Methods: Penile and cervicovaginal swabs were self-collected from 15- to 59-year-olds and tested for 37 HPV types. The 4vHPV-type (6/11/16/18) and non–4vHPV-type (any of 33 other types) prevalences were estimated by 3-year age group and participant characteristics. Average percent changes (APCs) in prevalence were estimated using segmented log-binomial regression. Results: Among females, a positive relationship between non–4vHPV-type prevalence and age was seen from 15–17 to 21–23 years (APC, 56.5), followed by a negative relationship through 30–32 years (APC, −13.2); thereafter, prevalence was not related to age. The 4vHPV-type prevalence was positively related to age through 24–26 years (APC, 56.9), then negatively related through 57–59 years (APC, −6.0). Among males, non–4vHPV-type prevalence had a positive relationship with age through 21–23 years (APC, 102.4) with a smaller positive relationship through 57–59 years (APC, 1.4). For both sexes, modeled joinpoints for 4vHPV-type prevalence occurred at older ages compared with joinpoints for non–4vHPV-type prevalence. Conclusions: Sex differences in age-specific non–vaccine-type HPV prevalence may reflect natural history and sexual behavior. Differences in vaccine-type and non–vaccine-type modeling results suggest vaccine impact as joinpoints occur in mid-late 20s for vaccine-type HPV but early 20s for nonvaccine types. These data can assist in refining HPV vaccination models and inform HPV vaccination practices and policy. Abstract : Sex differences in patterns of human papillomavirus (HPV) prevalence by age were observed for quadrivalent vaccine-type HPV and non–vaccine-type HPV. Patterns differed between vaccine-type and non–vaccine-type HPV prevalence suggesting vaccine impact.Supplemental digital content is available in the text.